The challenge of safeguards in the WTO - Piérola, Fernando, 1975- (Cambridge international trade and economic law, 2014)
"The Challenge of Safeguards in the WTO provides a comprehensive overview of the safeguard mechanism in the multilateral trading system. It explains at length its historical and conceptual foundations and elaborates on the various requirements for the imposition of safeguards and the conduct of safeguard investigations. The author draws on his practical experience in order to analyse WTO case law as developed by WTO panels and the Appellate Body and to provide practical suggestions for the resolution of various complex issues which have arisen in practice. He also considers the challenges faced by companies involved in this type of case"--